Meningkatkan kemampuan numerasi siswa SMP melalui model discovery learning berbantuan aplikasi canva - Zahara, Nida Ayu; Yuliani, Anik; Sariningsih, Ratna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study aims to determine the effectiveness of the Discovery Learning model in improving students’ numeracy skills. The research employed a mixed-methods approach with a Convergent Parallel design, in which quantitative and qualitative data were collected simultaneously. Quantitative data were obtained through pretests and posttests, while qualitative data were gathered through student interviews in the experimental class. The subjects consisted of two classes of 30 students each, namely an experimental class and a control class. The results show that the experimental class achieved a higher posttest average compared to the control class and successfully reached the mastery learning criteria, whereas the control class did not. In addition, student questionnaires indicated positive responses with a percentage above 75%. Therefore, Discovery Learning is effective in enhancing numeracy performance and fostering active student engagement in the learning process